2022
DOI: 10.21203/rs.3.rs-1275284/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of COVID-19 pandemic on bone and soft tissue tumor treatment: a single institution study

Abstract: Background: The spread of coronavirus disease 2019 (COVID-19) has caused severe damage to routine medical care. This study aimed to investigate the impact of COVID-19 on bone and soft tissue tumor treatment at a single center. Methods: A retrospective comparative study was conducted between two groups of patients who received treatment at Osaka City University Hospital during the peak of the COVID-19 pandemic (February-December 2020, Group C) and during the same period the previous year (February to December 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 10 publications
(13 reference statements)
0
7
0
Order By: Relevance
“…Ban et al reported a significantly longer period of hospital stay due to the requirement of performing CT scan prior to patient admissions and/or surgeries which have greatly impacted the Japanese economic footing. 7 Although a similar recommendation is being imposed in France, CT scan was not as practical to be regularly performed in real life. 28 …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Ban et al reported a significantly longer period of hospital stay due to the requirement of performing CT scan prior to patient admissions and/or surgeries which have greatly impacted the Japanese economic footing. 7 Although a similar recommendation is being imposed in France, CT scan was not as practical to be regularly performed in real life. 28 …”
Section: Discussionmentioning
confidence: 99%
“…Due to personnel limitation within the operating theater, this practice was unavailable which further restricted the type of surgery options. 7 Furthermore, in attempting to control COVID-19 transmission, maximum surgery duration in some medical centers had been limited and had surgeons to re-evaluate their treatment approach for malignant sarcoma patients. 5 , 20…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations